Advanced engineering fluid mechanics - Muralidhar, K (Alpha Science International Ltd, 2005)
The book offers a solid education in the subject of fluid mechanics. The treatment works upwards from Newton's equations into the seminal Navier-Stokes equations. From these, various physical configurations, like pipes and flat surfaces, are discussed. Exact solutions are derived, where possible, and approximate solutions where not